Networked Listening and Nodal Listening: A Listening Church through the Lens of José Casanova and Charles Taylor - Jose, Jeff Shawn (Asian Horizons, 2025)
This paper explores the imagery of networked listening and nodal listening as central to envisioning a synodal Church. Based on José Casanova’s sociological analyses of secularisation, deprivatisation, and globalisation, the paper highlights how networked listening fosters openness to plural public religions and global denominationalism. Employing Charles Taylor’s understanding of secularity as changing conditions of belief, nodal listening is proposed as a way for the Church to engage relationally with diverse worldviews. Together, these complementary listening modes enrich synodality as a dynamic practice of discernment, enabling the Church to journey with both its members and the wider human family in today’s complex global and secular contexts.